Analysis Of Irrigation Water Quality For Rice Field In Kauditan I Village, Kauditan District, North Minahasa Regency. - Siti Mutmaina Pondaag; Wiske Rotinsulu; Sofia Wantasen; Bobby J. V. Polii; Tommy B. Ogie; Frangky J. Paat; Jooudie N. Luntungan (Sam Ratulangi University, 2023)
The purpose of this study was to determine the quality of irrgation water in Kauditan 1 I Village. Based on PP No. 22/2021 Concerning the Implementation of Environmental Protection and Management, Appendix VI concerning Class II, III and IV National Water Quality Standards for irrigating plantations and Sodium Adsorption Ratio (SAR) values in Kauditan District, North Minahasa Regency. This research was carried out for Â± two months (2 months), from July to September 2022 in the village of Kauditan I, Kauditan District, then continued with analysis in the Manado Baristand Laboratory. The results showed that Total Dissolved Solid (TDS), Total Suspended Solid (TSS), Nitrate-N (NO3-N), Phosphate (PO4-P), Boron (B), Chloride (Cl) and pH met the National Water Quality Standard requirements. Class II, III and IV Designation for Irrigating Plantations Based on Government Regulation No. 22 of 2021 concerning Implementation of Environmental Protection and Management, Appendix VI. River Water and the Like. Electrical Conductivity meets Ayers & Westcot irrigation water quality requirements. (1985) with good category. And the value of Sodium Adsorption Ratio (SAR) is <10 with a good category. Keywords: Water quality, Irrigation, Rice fields, National Water quality standard Abstrak Tujuan penelitian ini adalah untuk mengetahui kualitas air irigasi di Desa Kauditan I Berdasarkan PP No. 22/2021 Tentang Penyelenggaraan Perlindungan dan Pengelolaan Lingkungan Hidup, Lampiran VI tentang Baku Mutu air Nasional Kelas II, III dan IV peruntukan mengairi pertanaman dan nilai Sodium Adsorption Ratio (SAR) di Kecamatan Kauditan Kabupaten Minahasa Utara. Penelitian ini dilaksanakan selama Â± dua bulan (2 bulan), mulai Juli hingga September 2022 di desa Kauditan I Kecamatan Kauditan, kemudian dilanjutkan dengan analisis di Laboratorium Baristand Manado. Hasil penelitian menunjukan Total DIssolved Solid (TDS), Total Suspended Solid (TSS), Nitrat-N (NO3-N), Fosfat (PO4-P), Boron (B), Klorida (Cl) dan pH memenuhi syarat Baku Mutu Air Nasional Kelas II, III dan IV Peruntukan Untuk Mengairi Pertanaman Berdasarkan Peraturan Pemerintah No. 22 Tahun 2021 Tentang Penyelengaraan Perlindungan Dan Pengelolaan Lingkungan Hidup, Lampiran VI. Air Sungai dan Sejenisnya. Daya Hantar Listrik memenuhi persyaratan kualitas air irigasi Ayers & Westcot. (1985) dengan kategori baik. Serta nilai Sodium Adsorption Ratio (SAR) adalah <10 dengan kategori baik. Kata kunci: Kualitas air, Irigasi, Persawahan, Baku Mutu Air Nasional